Investigation of functionally graded triply periodic minimal surfaces with graphene-reinforced AlSi10Mg powder: Design, fabrication and impact resistance - Mengyuan Hu; Xueqing Wu; Yangyang Xu; Xin Huang; Da Lu; Baoqing Pei (Materials & Design)
The triply periodic minimal surfaces (TPMS) are regarded as potential impact resistance structures due to the lightweight and outstanding energy absorption. Graphene is an ideal reinforcing phase material for the high strength and excellent ductility. However, the research on the effect of graphene, as a reinforcing phase, for the impact resistance of gradient TPMS is relatively limited. In this work, different gradients Diamond and Gyroid structures were designed to employ finite element analysis. The structures were prepared by SLM with optimized parameters and were performed with quasi-static compression and dynamic impact experiments. The impact performance was quantified by three critical indicators. The positive gradient porosity Gyroid structure (PGG) and positive gradient porosity Diamond structure (PGD) possessed superior energy absorption capacity. The samples prepared with optimized parameters of the laser powder of 370 W and scanning speed of 1500 mm/s exhibited significant characteristics with relative density of 99.6 %. The PGG and PGD lattice structures possessed superior impact resistance under both loading conditions, which the mechanical properties were improved by the load transfer, grain refinement, thermal expansion mismatch and Orowan strengthening mechanism of graphene. This study has guiding significance for the design of lightweight porous structures and enhancement of impact resistance.